Das Endgericht bei Paulus Framesemantische und exegetische Studien zur paulinischen Eschatologie und Soteriologie - Stettler, Christian (Mohr Siebeck, 2019)
In the 'New Perspective on Paul' the last judgment does not play any decisive role. According to other Pauline scholars, Paul, in his many fragmentary references to a last judgment, did not presuppose a consistent conception of judgment, but instead used different and sometimes contradicting motives in different contexts. Christian Stettler counters these views from a cognitive semantic perspective. Since in frame semantics language is seen as an 'access point' to encyclopaedic cognitive concepts, the author argues that judgement texts are references to a more detailed concept of the last judgement that Paul presupposed in his letters and taught in his churches. Stettler offers a full reconstruction of this concept by a semantic analysis of all relevant passages and through more extensive interpretation of central texts. The result is a reading of Paul that offers a way forward both to New Perspective and traditional confessional readings.